Mä lehden luin Yleisön suhde painettuun ja digitaaliseen sanomalehteen - Heikkilä, Heikki (Tampere University Press, 2023)
In the current digital media environment, legacy newspapers and their readers are often regarded as obsolete. For media executives and many journalists, the future of news is exclusively digital. Given the economic uncertainties facing the industry, news producers' eyes are focused on audience metrics and their capacity to shed light on readers' preferences. This book sets out to analyse news reading from the perspective of the audience. Employing interviews as well as the so called obsläs method, it examines how readers of two Finnish regional newspapers, Hämeen Sanomat and Karjalainen, navigate in three distinct architectures of the newspaper: printed, digital replica and online news application. The assumption underlying the analysis is that each of these user interfaces favour somewhat differing reading protocols and routines. The empirical analysis responds to the big question pondered by editors and publishers: Where are the readers? It appears that most of the participants of the study tended to move from one architecture to another depending on their contextual and situational needs. In this comparison, the strengths of a printed newspaper seemed evident for many, while the balance between the pros and cons of the digital environment was more mixed. In addition to reporting the findings of the empirical audience study, this book evaluates the future of newspapers in the context of economic statistics and media policies. While the newspaper business in Finland struggles with increasing costs and volatility of income, it may well rely on the robust newspaper reading culture among the Finnish reading public.